Montelukast in the initial therapy for cedar pollinosis - OISO, Masatake; KANZAKI, Yuichi; TANAKA, Fumiaki; HONDA, Tatsuya; ISOGAWA, Shuji; TORIYA, Takafumi; INDO, Naoya; EURA, Masao; TORIYA, Ryuzo; NAKANO, Koji (jibi to rinsho, 2012)
The mean cedar pollen count in Kumamoto Prefecture over the past 10 years has been approximately 2,000 grains/cm2. The leukotriene receptor antagonist (LTRA) montelukast was effective in the initial therapy for cedar pollinosis during the 2009 pollen season, when a massive dispersal of 4,289 grains/cm2 was observed. The present study applied the same initial therapy during the 2010 pollen season, which ultimately had a relatively low pollen count of 815 grains/cm2, and investigated whether the effectiveness of the initial therapy using montelukast varied depending on the level of cedar pollen dispersal. The subjects consisted of 82 patients with cedar pollinosis treated at one of 10 facilities in Kumamoto Prefecture between January and March 2010. Nasal symptoms were successfully controlled from the initiation of montelukast monotherapy to the end of the pollen season in a total of 54 patients (65.9%). This rate was higher than in 2009 (40.7%), thus suggesting that montelukast monotherapy had a higher rate of successful control of symptoms when the pollen count was low. In addition, an analysis of eight patients that received initial therapy using montelukast in both 2009 and 2010 showed that all four of the patients that responded in 2009 also responded in 2010, while three of the four patients that did not respond in 2009 also did not respond in 2010, when the pollen count was lower. These patients were thought to be “LTRA non-responders”, in other words patients for whom the effects of LTRA can not be expected regardless of the pollen count.